153k views
5 votes
-1/2(3x-4)+3x=5/6
Please help

User Pongpat
by
4.7k points

1 Answer

3 votes

Answer:

x = -7/9

Explanation:

The usual recommendation is to clear fractions first. Here, you can do that by multiplying both sides of the equation by 6.

6(-1/2(3x -4) +3x) = 6(5/6)

-9x +12 +18x = 5 . . . . . . . . . simplify

9x = -7 . . . . . . . . . . . . . . . . . subtract 12

x = -7/9 . . . . . .divide by 9

__

Another way to do this is to eliminate parentheses first.

-3/2x +2 +3x = 5/6

3/2x = -7/6 . . . . . . . . . collect terms, subtract 2

x = (-7/6)(2/3) = -7/9 . . . . multiply by 2/3

User Nihal
by
4.6k points